1992
DOI: 10.1038/clpt.1992.69
|View full text |Cite
|
Sign up to set email alerts
|

Long-term weight control study I (weeks 0 to 34)

Abstract: To investigate the value of anorexiant medications as an adjunct to other forms of weight control therapy, we studied 121 people in a 34-week, double-blind clinical trial of 60 mg extended-release fenfluramine plus 15 mg phentermine resin versus placebo added to behavior modification, caloric restriction, and exercise. Participants weighed 130% to 180% (154% +/- 1.2%, mean +/- SEM) of ideal body weight (1983 Metropolitan Life tables) and were in good health. By week 34, participants receiving active medication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(28 citation statements)
references
References 1 publication
0
27
0
1
Order By: Relevance
“…Thus, intensive group behavior modification, as provided in this and Weintraub's (37) study, does not appear to be necessary for successful weight loss with the fenfluramine-phentermine combination. Instead, our results strongly suggest that primary care providers could effectively treat obese individuals with a combination of medication and brief, protocolguided lifestyle modification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, intensive group behavior modification, as provided in this and Weintraub's (37) study, does not appear to be necessary for successful weight loss with the fenfluramine-phentermine combination. Instead, our results strongly suggest that primary care providers could effectively treat obese individuals with a combination of medication and brief, protocolguided lifestyle modification.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, acceptable candidates were referred to their family physicians, who completed a history and physical examination and determined if there were any contraindications to treatment. These included, in addition to major illnesses (i.e., hepatic, renal, cardiovascular, etc): essential hypertension (> 140/90 mm Hg); primary pulmonary hypertension; glaucoma; Types I or I1 diabetes; pregnancy or lactation; use of antidepressant medications; and the chronic use of nasal decongestants or any medications known to affect weight (37).…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity is a risk factor for the chronic development diseases such as heart disease, type 2 diabetes and certain types of cancer. It has reported that dieting; exercising, pharmacotherapy and surgery are the treatments [5][6][7]. The safest treatment for obesity is weight loss [4].…”
Section: Introductionmentioning
confidence: 99%
“…Anti-obesity drugs may be taken to reduce food desire or decrease fat absorption. If diet, exercise, and medication are not stringent effect, a gastric balloon and surgery may be used to reduce weight [5][6][7].…”
Section: Introductionmentioning
confidence: 99%